Correlation dependence of Persica vulgaris (Mill.) water status indicators on the background of hydrothermal stressers of moist subtropics of Russia - J. S. Abilfazova (Новые технологии)
The article presents the main results of long-term studies of Persica vulgaris (Mill.) plants grown on the Black Sea coast of the Krasnodar Territory. Collectible sorting of peach is carried out on an area of 0.5 hectares in the Scientific and Production Department of Subtropical and Southern fruit crops of the Institute at an altitude of 50-70 m above the sea level in model trees of varieties and clones of very early, early, middle and late maturation. To determine the varietal stability of peaches to unfavorable environmental conditions water regime indicators have been assessed. Physiological indicators that diagnose functional state of plants, their resistance to stress factors and yield have been revealed.